Applied Electromechanical Devices and Machines for Electric Mobility Solutions 2020
DOI: 10.5772/intechopen.89055
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Hybrid Electric Vehicle Fuel Consumption Model for Transportation Applications

Abstract: This study presents a simple power-based microscopic hybrid electric vehicle (HEV) fuel consumption model for use in microscopic traffic software and various connected and automated vehicle (CAV) applications, including eco-routing and eco-drive systems. While numerous HEV energy consumption models have been developed, these models are complex and require vehicle engine data deeming them difficult to implement and making them nontransferable. The proposed model was developed using empirical data for a 2010 Toy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Analyzed is the fuel need for mileage in thousands of kilometers over a period of several years. That is in opposite to short-term testssuch as WLTP and RDE, various specialist tests [14] or simulations [7].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Analyzed is the fuel need for mileage in thousands of kilometers over a period of several years. That is in opposite to short-term testssuch as WLTP and RDE, various specialist tests [14] or simulations [7].…”
Section: Introductionmentioning
confidence: 95%
“…However, it is still unsatisfactory. Hence the increasing use of the RDE test [4][5][6] or simulation [7]. This is indeed an emissions test [8,9], but can also be used to evaluate fuel consumption.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that a fuel/energy model was developed with a special interest in measuring fuel/energy consumption for transportation planning, transportation impact assessments, vehicle technology evaluations, traffic simulation models, and specific control conditions [14]. In order to be utilized for real-time CAV transportation applications, there are several requirements for an ideal fuel/energy consumption model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Where ECbus(t) denotes the instantaneous energy consumption rate for a diesel bus; α 0 , α 1 and α 2 are vehicle-specific model coefficients that should be calibrated for each vehicle; is the mass factor accounting for rotational masses, where a value of 0.1 is used for HDVs [56]; is the term related to gear ratio, which is assumed to be zero due to the lack of gear data; a(t) is the instantaneous acceleration level; R(t) is the resistance force on the vehicle as given by Equation (4). An energy consumption model for a HEV was developed in [57]. This model estimates the instantaneous energy consumption rates of an HEV using instantaneous vehicle operational input variables, including instantaneous vehicle speed, acceleration and roadway grade, which can be easily obtained from GPS devices or smartphones.…”
Section: Energy Consumption Model For Busesmentioning
confidence: 99%
“…However, the study in [57] only investigated the energy data from LDVs. There is no evidence proving that this model also works for HDVs such as hybrid buses.…”
Section: Energy Consumption Model For Busesmentioning
confidence: 99%